Unusual derivatives from Hypericum scabrum - Soroury, Sara (Sci Rep, 2021)
Three new compounds (1–3) with unusual skeletons were isolated from the n-hexane extract of the air-dried aerial parts of Hypericum scabrum. Compound 1 represents the first example of an esterified polycyclic polyprenylated acylphloroglucinol that features a unique tricyclo-[4.3.1.1(1,4)]-undecane skeleton. Compound 2 is a fairly simple MPAP, but with an unexpected cycloheptane ring decorated with prenyl substituents, and compound 3 has an unusual 5,5-spiroketal lactone core. Their structures were determined by extensive spectroscopic and spectrometric techniques (1D and 2D NMR, HRESI-TOFMS). Absolute configurations were established by ECD calculations, and the absolute structure of 2 was confirmed by a single crystal determination. Plausible biogenetic pathways of compounds 1–3 were also proposed. The in vitro antiprotozoal activity of the compounds against Trypanosoma brucei rhodesiense and Plasmodium falciparum and cytotoxicity against rat myoblast (L6) cells were determined. Compound 1 showed a moderate activity against T. brucei and P. falciparum, with IC(50) values of 3.07 and 2.25 μM, respectively.